Obesity in pregnancy: a retrospective prevalence-based study on health service utilisation and costs on the NHS. Issue 2 (27th February 2014) - Morgan, Kelly L; Rahman, Muhammad A; Macey, Steven; Atkinson, Mark D; Hill, Rebecca A; Khanom, Ashrafunnesa; Paranjothy, Shantini; Husain, Muhammad Jami; Brophy, Sinead T
Abstract : Objective: To estimate the direct healthcare cost of being overweight or obese throughout pregnancy to the National Health Service in Wales. Design: Retrospective prevalence-based study. Setting: Combined linked anonymised electronic datasets gathered on a cohort of women enrolled on the Growing Up in Wales: Environments for Healthy Living (EHL) study. Women were categorised into two groups: normal body mass index (BMI; n=260) and overweight/obese (BMI>25; n=224). Participants: 484 singleton pregnancies with available health service records and an antenatal BMI. Primary outcome measure: Total health service utilisation (comprising all general practitioner visits and prescribed medications, inpatient admissions and outpatient visits) and direct healthcare costs for providing these services in the year 2011–2012. Costs are calculated as cost of mother (no infant costs are included) and are related to health service usage throughout pregnancy and 2 months following delivery. Results: There was a strong association between healthcare usage cost and BMI (p<0.001). Adjusting for maternal age, parity, ethnicity and comorbidity, mean total costs were 23% higher among overweight women (rate ratios (RR) 1.23, 95% CI 1.230 to 1.233) and 37% higher among obese women (RR 1.39, 95% CI 1.38 to 1.39) compared with women with normal weight. Adjusting for smoking, consumption of alcohol, or the presence of any comorbidities did not materially affect the results. The total mean cost estimates were £3546.3 for normal weight, £4244.4 for overweight and £4717.64 for obese women. Conclusions: Increased health service usage and healthcare costs during pregnancy are associated with increasing maternal BMI; this was apparent across all health services considered within this study. Interventions costing less than £1171.34 per person could be cost-effective if they reduce healthcare usage among obese pregnant women to levels equivalent to that of normal weight women.